Strategic Management of Technological Innovation - A.Schilling Melissa (McGraw -Hill, 2005)
Strategic Management of Technological Innovation follows a step-by-step process to explore how to guide a company from its strategic dynamics through formulation to implementation. Numerous high-profile examples reveal ways in which state-of-the-art strategies have been successfully applied to real companies and products from Sony to Segway.